Prognostic Value of Lung Ultrasound in Aortic Stenosis - Szabó, István Adorján; Gargani, Luna; Morvai-Illés, Blanka; Polestyuk-Németh, Nóra; Frigy, Attila; Varga, Albert; Ágoston, Gergely (Frontiers in Physiology, 2022)
Background: Aortic stenosis (AS) is the most common primary valve lesion requiring intervention in Europe and North America. It has a prolonged subclinical period during which, as AS worsens, left ventricular adaptation becomes inadequate and impaired systolic and/or diastolic dysfunction may lead to overt heart failure (HF). The development of HF is an inflexion point in the natural history of AS. Pulmonary congestion is a cardinal feature in HF, and lung ultrasound (LUS) evaluation of B-lines has been proposed as a simple, noninvasive tool to assess pulmonary congestion. Aim: To assess the presence and the prognostic value of sonographic pulmonary congestion in patients with moderate or severe AS. Methods: 75 consecutive patients (39 women, mean age 73.85±7.7 years) with moderate or severe AS were enrolled. All patients underwent comprehensive echocardiography and LUS with the 28 scanning-site assessment. Patients were followed-up for 13,4±6 months to establish the prognostic value of LUS. A composite endpoint of death (of any cause), hospitalization for HF and intensification of loop diuretic therapy was considered. Results: We found a severe degree of B-lines (≥30) in 29.33% of patients. The number of B-lines correlated with the estimated pulmonary artery systolic pressure (p<0,001, r= 0.574) and increased along with NYHA class (p<0.05, rho=0.383). At multivariable analysis, B-lines ≥30, and mean gradient were the independent predictors of events (B-lines: 2.79 (CI 1.03-7.54), p=0,04; mean gradient: 1.04 (CI 1.01-1.07), p=0.004. Conclusion: Evaluation of B-lines is a simple, highly feasible method to detect pulmonary congestion in AS. The number of B-lines correlates with the hemodynamic changes caused by AS and with the functional status of patients. A severe degree of sonographic pulmonary congestion is associated with an increased risk of adverse events.